1994
DOI: 10.1038/ng0194-98
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of genes from complex sources of mammalian genomic DNA using exon amplification

Abstract: Modifications to exon amplification have been instituted that increase its speed, efficiency and reliability. Exons were isolated from target human or mouse genomic DNA sources ranging from 30 kilobases (kb) to 3 megabases (Mb) in complexity. The efficiency was dependent upon the amount of input DNA, and ranged from isolation of an exon for every 20 kb to an exon for every 80 kb of target genomic DNA. In these studies, several novel genes and a smaller number of genes isolated previously that reside on human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
149
1
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(154 citation statements)
references
References 50 publications
2
149
1
2
Order By: Relevance
“…Exon-trapping experiments were carried out as described previously (Buckler et al 1991;Church et al 1994) with minor modifications on the largeinsert bacterial clone contig. Preliminary experiments suggested that to detect rare splice events, 96 trapped products per large-insert bacterial clone needed to be sequenced (data not shown).…”
Section: Identification Of Transcribed Sequencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Exon-trapping experiments were carried out as described previously (Buckler et al 1991;Church et al 1994) with minor modifications on the largeinsert bacterial clone contig. Preliminary experiments suggested that to detect rare splice events, 96 trapped products per large-insert bacterial clone needed to be sequenced (data not shown).…”
Section: Identification Of Transcribed Sequencesmentioning
confidence: 99%
“…CsCl-purified genomic P1, BAC, and PAC DNAs were digested with BamHI, BglII, PstI, SacI, and XhoI, and 125 ng of each digest ligated into 500 ng of pSPL3 (Church et al 1994) (Life Technologies, Gaithersburg, MD) digested with the appropriate restriction enzyme and phosphatased with CIAP (U.S. Biochemical, Cleveland, OH). One-tenth of the ligation was used to transform XL1-Blue MRFЈ cells (Stratagene, La Jolla, CA) by electroporation.…”
Section: Exon Trappingmentioning
confidence: 99%
See 2 more Smart Citations
“…After Cos cells transfection, a mini library of the RT-PCR products was constructed for each cosmid as described by Church et al 11 The cosmids covering the XLP-D deletion were subcloned on the basis of a detailed restriction map 8 (and unpublished data, Yin L, 1998) and sequenced using Dye Primer cycle sequencing chemistry with an Applied Biosystems 377A automated DNA sequencer. Plasmid and cosmid end sequencing was performed using Dye Terminator sequencing chemistry with Taq polymerase together with T3/T7/Sp6 primers.…”
Section: Exon Trapping and Sequencing Of The Xlp-d Regionmentioning
confidence: 99%